1990
DOI: 10.3758/bf03197088
|View full text |Cite|
|
Sign up to set email alerts
|

Switching between memory and perception: Moving attention or memory retrieval?

Abstract: Weber, Burt, and Noll (1986) estimated that the time needed to switch attention between memory and perception was around 300 msec. The first two experiments in the present paper estimated switching time using a variation of their task. Subjects reported aloud lists of six items. The items were read ofT a computer screen (perception), recited from memory, or reported alternately from the two sources. The data show that the switching-time estimate is influenced by input/output compatibility, response-initiation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
60
1

Year Published

1993
1993
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(75 citation statements)
references
References 12 publications
14
60
1
Order By: Relevance
“…For example, Dark (1990) and Garavan (1998) have demonstrated that in normal participants, substantial processing costs are invoked by the requirement to select a particular item within working memory from among several represented elements. Following E. K. Miller (1999), Rowe, Toni, Josephs, Frackowiack, and Passingham (2000) have recently proposed that such "attentional selection" of an item within working memory is a core mechanism underlying executive functions, which is closely related to dorsolateral prefrontal activity.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Dark (1990) and Garavan (1998) have demonstrated that in normal participants, substantial processing costs are invoked by the requirement to select a particular item within working memory from among several represented elements. Following E. K. Miller (1999), Rowe, Toni, Josephs, Frackowiack, and Passingham (2000) have recently proposed that such "attentional selection" of an item within working memory is a core mechanism underlying executive functions, which is closely related to dorsolateral prefrontal activity.…”
Section: Discussionmentioning
confidence: 99%
“…It leaves many things unspecified. For example, it does not give any details on how perceptual and cognitive operations are coordinated, which is an interesting issue worth of further research (for a few studies on this issue, see Carlson et al, 1993;Dark, 1990;Weber et al, 1986).…”
Section: Evaluation Of the Theoretical Frameworkmentioning
confidence: 99%
“…Although the central control is crucial for problem solving, the current framework does not attempt to specify its details because it is not the current focus. The most important function of the central control that is unique to ER-based problem solving is the coordination of the interplay between perception and cognition: allocating and switching attention between internal and external representations, integrating internal and external information, and coordinating perceptual and cognitive operations (for a few studies on these issues, see Carlson, Wenger, & Sullivan, 1993;Dark, 1990;Weber, Burd, & Noll, 1986).…”
Section: Central Controlmentioning
confidence: 99%
“…-Accepted by previous editor, Geoffrey R. Loftus 1981), switches between perceptual stimuli and memorized lists (Carlson, Wenger, & Sullivan, 1993;Dark, 1990;Weber, Burt, & Noll, 1986), and switches between mental or task sets (Jersild, 1927;Laabs & Stager, 1976;Rogers & Monsell, 1995;Spector & Biederman, 1976).…”
Section: Attention Switchingmentioning
confidence: 99%